Incubators of quebec's enterprises (1993)
This article provides information on incubators of enterprises, specially those found in Quebec. Throught the 80s, the concept of enterprise incubators was introduced in America by economic development experts. Their goals were to leam the effects of unemployment resulting from either the shut down of industrial plants or the use of automatic production processes by large companies. Furthermore, they sought to create jobs for inmigrants. The most promising field of these experiences is in high-tech industrial development, specially in electronics, micro processors, and software for computer systems. This area also covers innovative industries.